Immunogenicity of chondrocyte sheets: a review - Li, Juncen; Sun, Huilin; Guan, Jiaqi; Li, Bohui; Jin, Chen; Xie, Shanhong; Liu, Yu (Frontiers in Immunology, 2025)
The chondrocyte sheet is a sheet-like cell structure obtained by separating in vitro expanded and fused autologous chondrocytes from the bottom of the culture dish by physical means. The cell sheet contains autologous chondrocytes, extracellular matrix secreted by chondrocytes, and connective structures established between cells and matrix, and between cells and cells. In cartilage tissue engineering, chondrocyte sheets technology has great potential for the treatment of cartilage defects. Chondrocyte sheets have a low immunogenicity because they avoid the immune reaction caused by scaffolding materials. However, chondrocyte sheets can still cause severe local tissue swelling in the short term after implantation, resulting in a poor patient experience. In individual cases, an inflammatory reaction may even occur, leading to resorption of the chondrocyte sheet. This may be immunogenetically related to chondrocyte membrane surface-associated antigens, components of the extracellular matrix secreted by chondrocytes, and various bioactive components in the culture medium used during in vitro chondrocyte culture. Therefore, in order to investigate the causes of local tissue swelling and immune-inflammatory reactions induced by the implantation of chondrocyte sheets, this article reviews the immunogenicity of chondrocyte-associated antigens, components of the extracellular matrix of cartilage, and the active components of the cell culture medium.